A strategic model for women entrepreneurs: Digital literacy, resources, and innovation in enhancing MSME performance - Zahwa, Almu; Sutjipto, Mohammad Riza; Salim, Dwi Fitrizal (Edelweiss Applied Science and Technology, 2025)
This study aims to develop a strategic framework to improve the performance of women-led Micro, Small, and Medium Enterprises (MSMEs) through digital transformation. It explores the relationships between digital literacy, company resources, digital innovation, and business performance. A quantitative method was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) on survey data from members of the Indonesian Businesswomen Association (IWAPI) in West Java. The findings demonstrate that both digital literacy and company resources have significant positive effects on business performance, with digital innovation playing a key mediating role. Specifically, businesses with higher levels of digital literacy and well-managed resources tend to implement more effective digital innovations, leading to improved operational efficiency, increased sales, and stronger market competitiveness. This research offers a practical contribution by highlighting the need for structured training and policy support to foster digital capabilities in women-led MSMEs. The proposed framework provides actionable insights for policymakers and organizations like IWAPI in formulating initiatives that promote sustainable digital entrepreneurship. The study concludes that enhancing digital readiness is vital for driving innovation and ensuring the resilience and competitiveness of women entrepreneurs in the evolving digital economy.